Proyecto de inversión de la franquicia “Farmacias Medicity” para la ciudad de Quito - Carrión Ruiz, Alexandra Patricia (2015)
This work was made based on an investigation to determine the feasibility of investing in a franchise of pharmacies in the city of Quito, which allowed the application of methods and techniques, the inductive method based on observation to see and hear through research in order to get clear information dare market research that identifies unmet demand and the technical study of the location of the company; deductive method with the data applied in surveys by representative sample of crops; statistical method with tabulated data to see survey results were obtained. Observation and survey, which addressed 400 people in the economically active population of Quito information that allowed the study of demand and supply study surveyed 265 pharmacy owners was used for data collection. In the market study in the city of Quito, after tabulating the surveys they were analyzed and determined the actual demand for the first year of life of 22.442.367 visits and an offer of 6.246.000 visits obtaining a 16.196.367 visits unmet demand. The company will have an installed capacity of 2.082.000 visits corresponding to 12,85% of unmet demand, the pharmacy began operation with 100% of their installed capacity, also the location of it to be located in Northern determined Quito, Kennedy sector, in the streets and Luis Gonzalo Zaldumbide Calisto. Determining the administrative study as a Limited Liability Company and a functional organizational structure with hierarchical levels was performed, it has internal manuals and franchise functions. The project reaches an investment of $ 168.794,04 dollars and will be financed 59% of total investment with a contribution of partners corresponding to $ 100.000 dollars and 41% with a loan that will keep the project with the Bank of Pichincha of $ 68.794,04 dollars a 5-year period to 15,18% annual interest. Operating costs for the first year are $ 609.118,47 dollars and revenues are $ 712.668,61 dollars with a profit of 2% franchise and 15% for partners, with the net income of $ 61.788,37 dollars. The breakeven point occurs when the company operates to 39,48% of its installed capacity and sales are of $ 281.357,77 dollars. The financial evaluation presents the following results, the net present value of the project is $ 92.312,53 dollars; the internal rate of return is 32,65%; the benefit cost is $ 1,17 dollars; the payback period of capital is done in 2 years 5 months and 4 days; sensitivity regarding the project supports an increase in costs of up to 6,89% and lower expenses to 4,50%. Therefore we conclude with the results that this project is a profitable business capable of generating financial resources and market positioning, contributing positively to the economy of the city and therefore the country